Analysis of Biology Textbooks Based on Science Literacy at Senior High Schools - Siregar, Abdul Malik (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study was to describe the scope and calculate the level of science literacy in high school biology textbooks class XII based on science literacy. The science literacy categories used are science as a body of knowledge, science as the nature of inquiry, science as a way of thinking, and the interaction of science, technology, and society. This research is qualitative research with descriptive methods. There were four biology textbooks sampled in this study. The data used in this study used primary data. Primary data sources were obtained through direct surveys of the four schools. Secondary data was obtained through the internet on the school data page. The data collection method in this study uses the documentation method. The data analysis used uses content analysis, which is a technique for collecting and analyzing the content of a text. The results of data analysis showed that the category of science as a body of knowledge amounted to 55.3%, science as the nature of inquiry amounted to 10%, science as a way of thinking amounted to 34%, and the interaction of science, technology, and society amounted to 0%. The data illustrates that the class XII biology textbooks used by some schools have described science literacy with a good category. It's just that the books generally emphasize more on the aspects of science as a body of knowledge and less on present science and technology.